DNA Methylation, Nuclear Organization, and Cancer - Madakashira, Bhavani P.; Sadler, Kirsten C. (Frontiers in Genetics, 2017)
The dramatic re-organization of the cancer cell nucleus creates telltale morphological features critical for pathological staging of tumors. In addition, the changes to the mutational and epigenetic landscape in cancer cells alter the structure and stability of the genome and directly contribute to malignancy. DNA methylation is one of the best studied epigenetic changes in cancer, as nearly every type of cancer studied shows a loss of DNA methylation spread across most of the genome. This global hypomethylation is accompanied by hypermethylation at distinct loci, and much of the work on DNA methylation in cancer has focused on how local changes contribute to gene expression. However, the emerging picture is that the changes to DNA methylation in cancer cells has little direct effect on gene expression but instead impacts the organization of the genome in the nucleus. Several recent studies that take a broad view of the cancer epigenome find that the most profound changes to the cancer methylome are spread across large segments of the genome, and that the focal changes are reflective of a whole reorganization of epigenome. Hallmarks of nuclear reorganization in cancer are found in the long regions of chromatin marked by histone methylation (LOCKs) and nuclear lamina interactions (LADs). In this review, we focus on a novel perspective that DNA methylation changes in cancer impact the global structure of heterochromatin, LADs and LOCKs, and how these global changes, in turn, contribute to gene expression changes and genomic stability.